2001
DOI: 10.1016/s0033-3549(04)50073-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring socioeconomic status/position in studies of racial/ethnic disparities: Maternal and infant health

Abstract: SYNOPSISObjective. Theoretical and empiric considerations raise concerns about how socioeconomic status/position (abbreviated here as SES) is often measured in health research. The authors aimed to guide the use of two common socioeconomic indicators, education and income, in studies of racial/ethnic disparities in low birthweight, delayed prenatal care, unintended pregnancy, and breastfeeding intention.Methods. Data from a statewide postpartum survey in California (N = 10,055) were linked to birth certificate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…First, White race was associated with both primary partner and non–primary partner violence, which is contrary to health and safety findings from the general population. 38 It is, however, consistent with results from Nyamathi et al, 3 who reported that homeless women living on the streets of Los Angeles, California, were more likely than sheltered women to be White and longer-term homeless. Together, these studies suggest that race operates differently in impoverished populations compared with the general population and affects risk for victimization among unstably housed women.…”
Section: Discussionsupporting
confidence: 85%
“…First, White race was associated with both primary partner and non–primary partner violence, which is contrary to health and safety findings from the general population. 38 It is, however, consistent with results from Nyamathi et al, 3 who reported that homeless women living on the streets of Los Angeles, California, were more likely than sheltered women to be White and longer-term homeless. Together, these studies suggest that race operates differently in impoverished populations compared with the general population and affects risk for victimization among unstably housed women.…”
Section: Discussionsupporting
confidence: 85%
“…SES is a multi-dimensional concept and other indicators of SES include: education, occupation, wealth, and area-based composite measures. These indicators are not necessarily interchangeable as they do not always correlate highly with each other; for example, the correlation between income and education has been reported to vary by ethnic group from 0.34 to 0.58, reflecting that income can vary at similar levels of education across different ethnic groups [14]. We selected household income as a measure of SES, based on our consideration of the most plausible causal pathway between the outcome variable of food insecurity and SES; since, income provides individuals and families with the necessary material resources and determines their purchasing power for accessing goods and services.…”
Section: Discussionmentioning
confidence: 99%
“…An SES score was generated for each participant from maternal age, years of education, race/ethnicity (non-Hispanic White, non-Hispanic Black, Hispanic White or Other) and median income of maternal zip code using unrotated factor analysis, also known as principal components analysis [30], with the following equation:where “Age” is the standardized maternal age at enrollment in years, “Education” is the standardized years of maternal education at enrollment, “Income” is the standardized logarithmic median household income of the mother’s zip code at enrollment, and “Race” is zero for mothers who self-identified as “non-Hispanic White” and “non-Hispanic Other;” and one for women who self-identified as “non-Hispanic Black” and “Hispanic White.” Maternal variables were selected based on prior research of important components of maternal SES [15] and a multivariate SES index in women with breast cancer [31]. One factor was retained based on Scree plot inspection (Additional file 3: Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…It is also a strong determinant of health [7] and has been repeatedly linked to diet quality [814]. Importantly, the association between SES and a health outcome can differ depending on how SES is measured [15]. Furthermore, the overall effect of SES cannot be accurately estimated when the highly collinear variables that determine SES are all added as covariates in a statistical model.…”
Section: Introductionmentioning
confidence: 99%